Assessment of the Diagnostic Performance of MUAC in Malnutrition Screening and Its Correlation with Other Anthropometric Indicators in Healthy Children and Adolescents - Hatice Esra Durukan; Burçe Emine Dörtkardeşler; Merve Tosyalı; Şule Gökçe; Nuri Zafer Kurugöl; Feyza Koç (Children)
Background/Objectives: This study aimed to evaluate the correlation of mid-upper arm circumference (MUAC) z-scores with body mass index (BMI) and weight-for-height (WFH) z-scores to determine its reliability in identifying malnutrition and its potential in clinical practice in healthy children and adolescents. Methods: Our study included 906 healthy children and adolescents aged between 2 months and 18 years who were admitted to University Hospital’s General Pediatrics Clinic and attended 12 primary schools in 6 additional Izmir provinces. Anthropometric measurements (weight, length/standing height, MUAC, BMI, WFH) were performed. The relationship between MUAC z-scores, BMI, and WFH z-scores of cases with malnutrition were evaluated. Results: According to the WHO BMI z-score classification, 6 (0.7%) of the children were defined as having severe undernutrition, 43 (4.7%) as moderate undernutrition, 146 (16.1%) as mild undernutrition, 486 (53.6%) as normal, 142 (15.7%) as overweight, and 83 (9.2%) as obese. At any age over two years, fair agreement was observed between MUAC z-scores and WHO BMI z-scores in defining malnutrition alone compared to other growth measures (weighted kappa = 0.371). Under two years of age, the correlation between MUAC z-scores and BMI z-scores showed moderate agreement in detecting overweight and obesity (weighted kappa = 0.479), and between MUAC and WHO WFH z-scores showed moderate agreement (kappa = 0.252). Conclusions: The study found a moderate and fair connection between MUAC z-scores and other criteria. However, further MUAC z-score screening and diagnostic power testing in larger pediatric populations are needed to validate its use alongside other key anthropometric indicators in malnutrition diagnosis. MUAC measurement should be popularized in routine pediatric outpatient clinics to detect malnutrition quickly.